IMPLEMENTASI THEORY OF PLANNED BEHAVIOR (TPB) PADA PENGUKURAN PERSEPSI PENDAPATAN BUNGA BANK KONVENSIONAL - Puji Lestari; Liana Dewi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
Knowledge about illegitimate of usury is growing rapidly in the community. Based on this knowledge, the community is motivated to make various efforts in avoiding usury, one of which is to avoid receiving bank interest from the deposit of funds in the bank. This research aims to study the factors that influence people's intentions and actions in avoiding bank interest income by using Theory of Planned Behavior (TPB) as a theoretical basis. The sample in this study amounted to 55 respondents who came from the usury-free community. Data was collected through a questionnaire consisting of 20 statements and analyzed with the Structural Equation Model (SEM). The test results state that attitudes negatively affect individual intentions to avoid bank interest income while subjective norms have the opposite effect, the similarity of the two is a less powerful effect. Perceived behavioral control has a positive and strong influence on intentions, as well as intentions that influence individual avoidance of bank interest income.